Unveiling the dynamic trends of plant-derived exosome nanovesicles-based theranostics: through bibliometric and visualized analysis - Siyang Cao; Siyang Cao; Yingchen Pang; Yingchen Pang; Yihao Wei; Yihao Wei; Yihao Wei; Deli Wang; Deli Wang; Ao Xiong; Ao Xiong; Jun Yang; et al. (Frontiers in Medicine)
Plant-derived exosome nanovesicles (PDENs) have emerged as eco-friendly, sustainable and highly efficient platforms for drug delivery, attracting significant attention in biomedical research. As a consequence, PDENs have become a focus for multidisciplinary investigation. Despite extensive research, impartial and comprehensive evaluations of PDENs-based theranostic applications remain scarce. This study fills this gap by using bibliometric techniques to systematically analyze 15 years of scientific publications. The analysis is based on data retrieved from the Web of Science Core Collection, covering studies published from 2009 to 2024. Advanced bibliometric tools and visualization techniques were utilized to ensure a rigorous and detailed analysis. The results highlight China’s dominant position, contributing 35.09% of all publications, thereby significantly influencing the research trajectory in this field. Key contributions have been made by institutions such as the Nanjing University of Chinese Medicine, the Chinese Academy of Sciences and Zhejiang University, with Stefania Raimondo emerging as the most productive researcher. International Journal of Molecular Sciences stands out as the journal with the largest number of publications in this area. The study also identifies key related diseases, including colonic diseases, vascular diseases, osteosarcoma and DNA virus infections, etc. In conclusion, this study offers a detailed assessment of advancements and evolving patterns in PDENs-based theranostics over the past 15 years. It emphasizes critical areas that require further focus and systematic exploration by the scientific community. Additionally, this analysis identifies major research hotspots and emerging boundaries, providing scholars and research institutions with strategic insights to shape future studies.